1992
DOI: 10.1007/bf00146379
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the presence of spotted fever group rickettsiae in dogs and dog ticks of the central provinces in Spain

Abstract: To assess canine exposure to spotted fever group rickettsiae in the central provinces of Spain, ticks removed from dogs were studied by immunofluorescence (IF) staining. Twenty-eight out of 65 (43.0%) samples from ticks were positive. Sera from 58 dogs were also collected and the presence of antibodies to Rickettsia conorii studied. Thirty-four (58.6%) dogs presented significant titers by IF. Surveillance data from these provinces show the presence of Boutonneuse fever cases during recent years, evidence that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
0
11
0
2
Order By: Relevance
“…In addition, R. rhipicephali, a close phylogenetic relative of R. massiliae (30,(53)(54)(55)(56)62) has also been detected in R. sanguineus ticks in Spain (33), Portugal (4), France (22), and the African continent (63). In these countries, particularly in Greece and Spain, it has been noted that a discrepancy exists between the sero- prevalence of antibodies to spotted fever group rickettsiae in local human populations, the incidence of reported rickettsioses (3,17,28,32,60), and the occurrence of severe and fatal forms of MSF (28,29,34,57,62). Similarly, there is a noticeable discrepancy in the prevalence of antibodies reactive with virulent R. conorii in dog populations and the occurrence of disease in different locations in Spain (32,34,60,61).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, R. rhipicephali, a close phylogenetic relative of R. massiliae (30,(53)(54)(55)(56)62) has also been detected in R. sanguineus ticks in Spain (33), Portugal (4), France (22), and the African continent (63). In these countries, particularly in Greece and Spain, it has been noted that a discrepancy exists between the sero- prevalence of antibodies to spotted fever group rickettsiae in local human populations, the incidence of reported rickettsioses (3,17,28,32,60), and the occurrence of severe and fatal forms of MSF (28,29,34,57,62). Similarly, there is a noticeable discrepancy in the prevalence of antibodies reactive with virulent R. conorii in dog populations and the occurrence of disease in different locations in Spain (32,34,60,61).…”
Section: Discussionmentioning
confidence: 99%
“…In these countries, particularly in Greece and Spain, it has been noted that a discrepancy exists between the sero- prevalence of antibodies to spotted fever group rickettsiae in local human populations, the incidence of reported rickettsioses (3,17,28,32,60), and the occurrence of severe and fatal forms of MSF (28,29,34,57,62). Similarly, there is a noticeable discrepancy in the prevalence of antibodies reactive with virulent R. conorii in dog populations and the occurrence of disease in different locations in Spain (32,34,60,61). These observations support the idea that both virulent and avirulent rickettsiae may be responsible for seroreactivity to spotted fever group agents in human and canine populations (9,10,17).…”
Section: Discussionmentioning
confidence: 99%
“…Reports dealing with the resurgence of MSF in Spain in the early 1980s (31,33,45) have been behind the origin of several clinical studies of the disease and serosurveys in humans and dogs (16,20,22,25,31,(42)(43)(44)(45)(46). So far, the two strains isolated in Spain have been identified as R. conorii in Catalonia and R. rhipicephali in the region of Madrid (17,23,39).…”
Section: Discussionmentioning
confidence: 99%
“…In Spain, several cases of the disease have been described from all over the country, and serosurveys have been conducted in different areas (16,19,20,22,25,31,42,44,45). These studies indicated that epidemiological data recorded in the Catalan region differ from those recorded in other Spanish or Mediterranean regions.…”
mentioning
confidence: 99%
“…5 In the central area of Spain, where many cases of MSF are currently diagnosed, this same parallelism between human cases and canine prevalence has also been observed. 8 Some authors have found seasonal differences in seroprevalence rates in dogs, suggesting the possibility that antibody titer may not persist in these animals. 9 Therefore, the purpose of this study was to assess the antibody titer to R. conorii in dogs, over a prolonged period of time.…”
mentioning
confidence: 99%